Examen especial a la cartera de crédito de la cooperativa de ahorro y crédito “acción y desarrollo”, durante el período 2016. - Paguay Cacuango, Clara Inés (2017)
The credit union of savingsand loan “Acción y Desarrollo” Ltda., is a financial institution that provides services for the benefit of its members. It is located on Isabel de Godín Avenue and Francia Street (two blocks from the la Condamine Shopping center). The present research work is a special examination of loans portfolio of the credit union of savings and loan “Acción y Desarrollo” Ltda., during the period 2016, it includes the following processes; regarding the theoretical framework deals with all the theory underlyng the present research project, as well as the scientific foundations that serve as the basis for it, the background of the company, theoretical basis is defined about the special examination, concept, types and phases of the same, internal control, evaluation methods, concept of loans portfolio, concept of credit, credit characteristics, credit requirements, lines of credit, types of credit, credit classification and risk of credit. The methodological framework consists of the methods of research, research types, research design, population and sample, techniques and instruments, procedures for the analysis of the results of the execution of the special examination are developed. Finally, with regard to the conclusions and recommendations, it is determined the importance of the special examination of the loan portfolio for of the credit union of savings and loan “Acción y Desarrollo” Ltda., the same will be directed towards the main officials for an improvement in decision – making.